ANALYSIS OF NEEDS FOR DEVELOPING TEACHING MATERIALS FOR WRITING ADVERTISING TEXTS BASED ON ANDROID PLATFORM APPLICATIONS FOR CLASS VIII STUDENTS - Muhamad Faisal Assyuza; Miftahulkhairah Anwar; Gusti Yarmi (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This research is motivated by the low ability of students to write attractive advertising texts. This is because the teaching materials available in schools are not yet able to facilitate students being able to write text advertisements well. The research carried out in this study was descriptive qualitative research, namely to describe students' needs for teaching materials that suit the students' needs